2004
DOI: 10.1038/sj.emboj.7600138
|View full text |Cite
|
Sign up to set email alerts
|

Roles of histone acetylation and chromatin remodeling factor in a meiotic recombination hotspot

Abstract: Histone acetyltransferases (HATs) and ATP-dependent chromatin remodeling factors (ADCRs) are involved in selective gene regulation via modulation of local chromatin configuration. Activation of the recombination hotspot ade6-M26 of Schizosaccharomyces pombe is mediated by a cAMP responsive element (CRE)-like sequence, M26, and a heterodimeric ATF/CREB transcription factor, Atf1 . Pcr1. Chromatin remodeling occurs meiotically around M26. We examined the roles of HATs and ADCRs in chromatin remodeling around M26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
1
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(201 citation statements)
references
References 42 publications
9
187
1
4
Order By: Relevance
“…In an analysis of the ade6-M26 hotspot in S. pombe, Yamada et al (12) reported that loss of the SpGcn5 histone acetylase or deletion of the Snf22 histoneremodeling proteins reduced the activity of the hotspot. Since the loss of a histone acetylase would be expected to decrease acetylation at the ade6-M26 hotspot, the mechanism by which loss of SpGcn5 reduces hotspot activity may be related to the mechanism by which loss of Set2p, Rpd3p, and Hda1p stimulate hotspot activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of the ade6-M26 hotspot in S. pombe, Yamada et al (12) reported that loss of the SpGcn5 histone acetylase or deletion of the Snf22 histoneremodeling proteins reduced the activity of the hotspot. Since the loss of a histone acetylase would be expected to decrease acetylation at the ade6-M26 hotspot, the mechanism by which loss of SpGcn5 reduces hotspot activity may be related to the mechanism by which loss of Set2p, Rpd3p, and Hda1p stimulate hotspot activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some mutants that affect chromatin modifications reduce the frequency of meiosis-specific DSBs. In the yeast S. pombe, mutations in a histone acetylase or in a chromatin-remodeling activity reduce the activity of the ade6-M26 recombination hotspot (12). In S. cerevisiae, loss of Set1p (a histone methyltransferase) or Rad6p (a ubiquitin-conjugating enzyme) reduce DSB formation (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Long repeats including LINE-1 elements are normally heavily DNA-methylated (Woodcock et al, 1988;Crowther et al, 1991;Woodcock et al, 1997), a feature of heterochromatin. DNA methylation (and heterochromatin in general) has been reported to suppress homologous recombination (Pàldi et al, 1995;Maloisel and Rossignol, 1998;Schnable et al, 1998;Fu et al, 2002;Yao et al, 2002;Yamada et al, 2004;Myers et al, 2005) as well as transposition (Yoder et al, 1997;Walsh et al, 1998;Hirochika et al, 2000;Robertson, 2001;Bird, 2002;Kato et al, 2003). Accordingly, reports of deletions caused by homologous recombination between LINE-1 elements are rare (Segal et al, 1999) except in cancers (Florl and Schulz, 2003) where LINE-1 elements are frequently hypomethylated (Santourlidis et al, 1999;Takai et al, 2000;Ehrlich, 2002;Carnell and Goodman, 2003;Florl et al, 2004;Roman-Gomez et al, 2005).…”
Section: Non-random Repeat Distributions Via Natural Selectionmentioning
confidence: 99%
“…Histone acetylation is among the most studied epigenetic modifications. Acetylation of histones is generally associated with transcriptional activation; however, this modification is also involved in repression of transcription, DNA repair, DNA replication and recombination (Eberharter and Becker, 2002;Carrozza et al, 2003;Yamada et al, 2004). Core histones H3 and H4 are the main subjects of this modification and can be acetylated at various lysine residues, the amount and specific location of which is controlled by the antagonistic action of histone acetyltransferases (HATs) and histone deacetylases (HDACs).…”
Section: Introductionmentioning
confidence: 99%